2010
DOI: 10.1111/j.1600-079x.2010.00784.x
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the minimal melatonin exposure required to induce osteoblast differentiation from human mesenchymal stem cells and these effects on downstream signaling pathways

Abstract: The purpose of this study was to determine the critical time periods of melatonin treatment required to induce human mesenchymal stem cells (hAMSCs) into osteoblasts and to determine which osteogenic genes are involved in the process. The study design consisted of adding melatonin for different times (2, 5, 10, 14 or 21 days) toward the end of a 21-day treatment containing osteogenic (OS+) medium or at the beginning of the 21-day treatment and then withdrawn. The results show that a 21-day continuous melatonin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
149
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(167 citation statements)
references
References 80 publications
15
149
1
2
Order By: Relevance
“…The results of this study indicated different result from the one conducted by Radio et al (2006), Zaminy et al (2008) and Sethi et al (2010). These studies showed that the levels of ALP produced by osteoblast cells in the group provided with melatonin were higher than the group that were not provided with melatonin.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…The results of this study indicated different result from the one conducted by Radio et al (2006), Zaminy et al (2008) and Sethi et al (2010). These studies showed that the levels of ALP produced by osteoblast cells in the group provided with melatonin were higher than the group that were not provided with melatonin.…”
Section: Discussioncontrasting
confidence: 56%
“…Study conducted by Feskanich et al (2008) states that low melatonin levels in more than 38,000 postmenopausal women who worked at night for more than 20 years significantly contribute to osteoporosis and the risk of suffering fractures in forearm and pelvis. Meanwhile, administration of melatonin is known to improve the mechanism of bone remodeling in BMMSCs (Radio et al 2006;Sethi et al 2010). Thus, this study was conducted to explain the elevation of osteoblast activity found in cultured BM-MSCs in the medium of osteogenic exposed with melatonin in physiological dosage, so it can be used as a scientific base to develop therapies for diseases that require increased osteoblast activity, such as osteoporosis.…”
Section: Introductionmentioning
confidence: 99%
“…[14] Melatonin increases pre-osteoblast/osteoblast/osteoblastlike cell proliferation, promotes the expression of type I collagen and bone marker proteins interthread bone is an intermediate situation of new bone in with the implant by stimulation of osteoblasts and the old bone in the total peri implant area by osteoclast inhibition, and melatonin continues its activity passing on from the 2 nd to the 5 th week and to the 8 th week. [14][15][16] Arat Bilhan et al (2015) they said that use of a splinted attachment can be preferred to reduce forces emerging around the implants. The use of 2 solitary attachments in cases with good bone quality and ideal sized implants are safe with the bilateral loading on over dentures.…”
Section: Discussionmentioning
confidence: 99%
“…In support of this association, the Melatonin Osteoporosis Prevention Study (MOPS; NCT01152580) revealed that melatonin improved bone health in perimenopausal women by renormalizing bone marker turnover [17]. Previous work also from the Witt-Enderby group has shown a role for MT 2 melatonin receptors in melatonininduced mesenchymal stem cell differentiation into osteoblasts [18,19]. Exposure to artificial light at night affects melatonin production but may also affect bone physiology possibly through reduction in melatonin levels.…”
Section: Introductionmentioning
confidence: 97%
“…To demonstrate this association, a recent study has shown that female nightshift workers exposed to artificial light at night, a known suppressor of melatonin production, had an increased risk of hip and wrist fractures over the eight years of follow-up compared to cohorts that worked the day shift [20]. Moreover, melatonin may be a potential treatment option because pre-clinical research has shown it impacts bone metabolism by promoting osteoblast differentiation and activity [15,18,19,21,22] and by suppressing osteoclast activity via increasing osteoprotegrin and actions on receptor activator NF-κB ligand (RANKL) [15,23]. Also, when taken orally, melatonin is welltolerated and has a high safety profile.…”
Section: Introductionmentioning
confidence: 99%